2017
DOI: 10.1002/ecy.1793
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in nitrogen uptake among plant species with contrasting nutrient acquisition strategies in a tropical forest

Abstract: Nitrogen (N) availability influences the productivity and distribution of plants in tropical montane forests. Strategies to acquire soil N, such as direct uptake of organic compounds or associations with root symbionts to enhance N acquisition in exchange for carbon (C), may facilitate plant species coexistence and ecosystem N retention. Alternatively, rapid microbial turnover of soil N forms in tropical soils might promote flexible plant N-uptake strategies and mediate species coexistence. We tested whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 81 publications
0
31
0
1
Order By: Relevance
“…AM fungi) that host different mycorrhizal types (Nasto et al., ; Steidinger et al., ). In contrast, another study on more fertile soil only provided weak evidence for N partitioning among tropical tree species with different mycorrhizal types (Andersen, Mayor, & Turner, ). It is possible that the N partitioning we observed is more common on soils with low overall N availability than on N‐rich soils.…”
Section: Discussionmentioning
confidence: 97%
“…AM fungi) that host different mycorrhizal types (Nasto et al., ; Steidinger et al., ). In contrast, another study on more fertile soil only provided weak evidence for N partitioning among tropical tree species with different mycorrhizal types (Andersen, Mayor, & Turner, ). It is possible that the N partitioning we observed is more common on soils with low overall N availability than on N‐rich soils.…”
Section: Discussionmentioning
confidence: 97%
“…Tropical and subtropical ecosystems usually have higher N cycling rates compared with high‐latitude and high‐altitude ecosystems where N mineralization and nitrification are generally lower and plants rely more on organic N sources (Elser et al., ; Liu et al., ; Vitousek et al., ; von Felten et al., ). Until now, most studies on plant N uptake in tropical ecosystems have stressed inorganic N due to its much higher availability than organic N (Andersen, Mayor, & Turner, ; Craine et al., , ; Houlton et al., ). Moreover, plant dissolved organic nitrogen (DON) use was often demonstrated experimentally by the uptake of one or a few 15 N‐labelled amino acids, which cannot elucidate the real availability of the whole soil DON pool to plants (Kahmen, Livesley, & Arndt, ), so that substantial uncertainties existed in the source contributions estimated by using the δ 15 N of the whole DON pool (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, we assume NH 4 + and NO 3 − to be the dominant N sources for plants in tropical ecosystems (e.g. Andersen et al., ; Houlton et al., ), and use a δ 15 N mass balance between leaf N and source N (referred to Houlton et al., ; Equation ) to evaluate the fractional contributions of soil NH 4 + (fnormalNH4+) and NO 3 − (fnormalNO3) to plant N by considering isotope effects during plant N uptake and assimilation (ε). δ 15 normalN normalleaf = false( normalδ 15 N normalNH 4 + × f normalNH 4 + + normalδ 15 N normalNO 3 × f normalNO 3 false) ε where 1 = fNH4++fNO3 and ε = ε u + ε i × [L below /(L above + L below )]. The ε u denotes the isotope effects during root N uptake, ε i denotes the isotope effects between N sources of the whole plant and leaves due to differing N allocation/assimilation between above‐ and below‐ground tissues (Houlton et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Cornell et al (2003) and Cornell (2011) collected available studies over the world and revealed that WSON/TDN ratio in precipitation exhibited a large range with the typical ratios ranging from 25% to 35%. There are increasing number of studies which revealed that plant uptake of organic N, particularly low molecular weight amino acids, occurs widely in low N ecosystems (Andersen et al, 2017;Kielland, 1994;Kielland et al, 2006). Kielland (1994) revealed that the uptake rates of glycine and ammonium by plants in arctic tundra are comparable.…”
Section: Introductionmentioning
confidence: 99%